SYMMETRY REDUCTION OF THE ALUMINOSILICATE FRAMEWORK OF LAU TOPOLOGY BY ORDERING OF EXCHANGEABLE CATIONS: THE CRYSTAL STRUCTURE OF PRIMARY LEONHARDITE WITH A PRIMITIVE BRAVAIS LATTICE - Baur W.H.; Joswig W.; Fursenko B.A.; Belitsky I.A. (My University, 1997)
Primary leonhardite, Ca2.55K1.59Na1.24Fe0.03Al 8.19Si15.87O48 · 13.93H2O, with a primitive Bravais lattice, is a leonhardite that cannot be hydrated and is not formed by the dehydration of laumontite. It crystallizes in space group P 12/a1 with a = 14.556(4) Å, b = 13.206(3) Å, c = 7.513(3) Å, β = 110.75(2)°, V = 1351(1) Å3 and Z = 1. Even though P 12/a1 is a subgroup of C 12/m1 (the space group of laumontite and secondary leonhardite), the geometry of the aluminosilicate framework and the distribution of Al and Si atoms in primary leonhardite are extremely close to what is known for laumontite (Ca4Al8Si16O48 · 18H2O) and partly dehydrated laumontite (Ca4Al8Si16O48 · 14H2O). Because Na and K substitute for Ca in the pores of primary leonhardite in an ordered way, its symmetry is reduced compared with laumontite. Because the total number of pore-filling cations is larger than in any other known laumontite (due to the replacement of Ca by univalent cations) primary leonhardite cannot accomodate as many water molecules in its pores as laumontites.